Wavelets in a problem of signal processing - Soares, Wendel Cleber; Villarreal, Francisco [UNESP]; Duarte, Marco Aparecido Queiroz; Filho, Jozué Vieira [UNESP] (My University, 2011)
In this work a new method is proposed for noise reduction in speech signals in the wavelet domain. The method for signal processing makes use of a transfer function, obtained as a polynomial combination of three processings, denominated operators. The proposed method has the objective of overcoming the deficiencies of the thresholding methods and the effective processing of speech corrupted by real noises. Using the method, two speech signals are processed, contaminated by white noise and colored noises. To verify the quality of the processed signals, two evaluation measures are used: signal to noise ratio (SNR) and perceptual evaluation of speech quality (PESQ).
Keywords: Discrete wavelet transform; Noise reduction; Polynomial combination